2005
DOI: 10.1136/hrt.2004.035733
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial cytokine gene expression is higher in aortic stenosis than in idiopathic dilated cardiomyopathy

Abstract: Objective: To investigate cytokine gene expression in patients with aortic valve stenosis (AS) and with idiopathic dilated cardiomyopathy (DCM), and to correlate wall stress with myocardial proinflammatory cytokine gene expression. Methods: Human left ventricular (LV) myocardial biopsies were obtained for subsequent reverse transcription polymerase chain reaction of tumour necrosis factor a (TNFa), interleukin (IL) -1b, and IL-6 mRNA. The study population consisted of 24 patients with AS and 10 patients with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…This is consistent with clinical evidence for a greater degree of inflammation associated with compensatory hypertrophy during early aortic stenosis when compared with decompensated HF groups. 38 Therefore, NFκB may mediate temporal and model-specific effects that are differentially modulated by altered myocardial eicosanoid levels and membrane PUFA composition.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with clinical evidence for a greater degree of inflammation associated with compensatory hypertrophy during early aortic stenosis when compared with decompensated HF groups. 38 Therefore, NFκB may mediate temporal and model-specific effects that are differentially modulated by altered myocardial eicosanoid levels and membrane PUFA composition.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental induction of hemodynamic overload in the adult mammalian heart has been shown to provoke a transient increase in pro-inflammatory cytokines (2). Furthermore, cardiac-specific over expression of IL-6 and TNF-α in mice hearts has been shown to develop cardiac hypertrophy and ventricular dysfunction similar to that seen in human disease conditions, suggesting that cytokines are critically involved in the cardiac remodeling process (9,30).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned cytokines play a dual role, activating apoptosis in myocytes (13), while also functioning in a cytoprotective manner (15). Furthermore, inappropriate activation of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) have been recognized as an important mediator in the development of endothelial dysfunction, cardiac hypertrophy, and heart failure in experimental animal models and in humans (9,17,28,30). Atrial natriuretic peptide (ANP) has been shown to inhibit the TNF-α induced adhesion molecule expression in endothelial cells (32).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicate that the activation of hypertrophic markers, matrix metalloproteinases (MMPs), and proinflammatory cytokines play a central pathophysiological roles in the development of cardiac hypertrophy, fibrosis, and heart failure in the experimental animal models and humans (11,52,58,66). Previous studies have suggested that ANP/ NPRA signaling acts as a negative regulator of inflammation and hypertrophic growth (14,65,67,69).…”
mentioning
confidence: 99%